Timbre in the Musical Performance as a Result of Audio-Mental Operations (Global Journal of Human-Social Science, 2021)
The aim of this paper is to reveal the relationship between the timbre, i.e. sound quality, obtained by an instrumentalist when playing a music piece, and the role of the hearing, listening, and other musical specific mental operations that take place in the brain of the instrumentalist during the performance, with the focus on the classical music, which depends in the most cases on the score. The timbre is a characteristic of every instrument or voice that makes their tone unique. It is given by the different sound components (partials) with different frequencies and amplitudes. The number and the amplitude of the partials are different from instrument to instrument; they depend on the construction of the instrument and on the art of playing, the last being the point in this article. It is known that timbre has an emotional impact on the perception. Its semantic features are represented through descriptors as: dark, bright, round, dull, dry, harsh, etc. that have to be created by the performers, in order to affect the auditory. Thus, they have to possess a good technique, able to get different timbres. Although, the technique has to be subordinated to the capacity of hearing in advance the sound with all its features: pitch, duration, intensity and timbre.